Study on the Stability of Large Retrogressive Landslide and Treatment Technology - Jiang, Guan; Feng, Zhongju; Zhao, Ruixin; Chen, Yuanmeng; Liu, Xiaofei (Journal of Engineering and Technological Sciences, 2024)
To study the catastrophic mechanisms of retrogressive landslides and assess the stability post treatment, it is essential to examine the internal factors contributing to landslides. This involves a detailed analysis of the characteristics of engineering geology, environmental conditions, and the impact of engineering construction activities on the landslide area. The comprehensive treatment schemes for landslides are determined using deep displacement monitoring and numerical analysis. It has been shown that the process of the landslide mechanism can be divided into four stages, i.e., primary structure breakage, rock mass damage deterioration, rock mass softening in water, and rainfall-induced instability failure. Rock mass damage and rainfall caused by slope excavation are the main causes and inducements of landslide instability. The monitoring results of deep displacement have shown that the sliding surface of a landslide is fully integrated. To mitigate the risk of secondary disasters, this study proposes a comprehensive set of measures based on the mechanisms of landslide instability and the support principle of a compensated traction zone. These measures include the implementation of prestressed anti-slide piles, the application of molten steel pipe grouting, and enhanced drainage techniques. The displacement of the slope was reduced, showing that the treatment scheme had a good reinforcement effect.